Analisis Product Life Cycle (PLC) Untuk Menentukan Strategi Pemasaran Pada Produk Bumbu Barokah Jember - Wulandari, Sri (LPPM Universitas PGRI Argopuro Jember, 2024)
High competition with the same product makes it very difficult to increase sales. In facing very tight market share competition, the right strategy is needed to maintain sales levels and be able to dominate the existing market share. In this research, researchers analyzed the position of barokah spices using the Product Life Cycle (PLC) to determine the marketing strategy to be used. The results of the Product Life Cycle analysis research show that the position of barokah seasoning is in a growth position. The marketing strategy applied for barokah seasoning expands product marketing so that the product is known to many consumers as well as expanding market share. In the face of intense competition with the same products, Barokah Spices continues to improve the quality of its spices and is able to innovate and create unique spices that can differentiate it from its competitors' spices. Marketing strategy targeting affordable prices.